Analisis Perbandingan Peramalan Anggaran Pengelolaan Sampah dengan Metode ARIMA, Exponential Smoothing, dan Least Square dalam Meningkatkan Green economy Kota Bandung - Marshela, Chindy; Hutapea, Riauli Susilawaty (Indonesian Accounting Research Journal, 2025)
Environmental degradation caused by waste problems in Bandung City requires preventive action through the implementation of a waste management program based on the principles of a green economy. The execution of this program requires funding; however, the budget has not been stable to date. This study aims to forecast the waste management budget of Bandung City for the years 2025–2026. This research is a descriptive study with a quantitative and qualitative approach. The forecasting methods used in this research are ARIMA, Exponential Smoothing, and Least Squares. Data collection was carried out by obtaining waste budget data for the years 2018–2024 from the Performance Accountability Report of Government Agencies (LKIP) of the Environmental and Sanitation Agency of Bandung City. Data analysis was performed using EViews 12. The results indicate that ARIMA is the best forecasting method, with the lowest MAPE value compared to the other two methods, at 2.71%.